A POTENTIAL USE OF A LANDSCAPE INTEGRATED MANAGEMENT TOOL TO MEASURE THE PROGRESS TOWARDS SUSTAINABILITY: A TRIAL APPLICATION AT THE GRAPE-PRODUCING COMPANY HÉTSZŐLŐ –TOKAJ REGION – DEBRECEN - HUNGARY - Garcia Torres, Sergio; Szőllősi, Nikolett; Qorri, Dejsi (Applied Studies in Agribusiness and Commerce, 2024)
Sustainable integrated management at the landscape scale is increasingly becoming paramount for the private, and public sectors, as these sectors recognize the high relevance of promoting integrated and collaborative management in their operating areas and territories. There has been no attempt to apply this approach in the current sustainability reporting frameworks. this paper aims to run a trustful assessment at the Hétszölö viticulture company to make sustainability claims. This paper applies a new way of reporting sustainability by selecting and assessing suitable indicators within the Ecosystem, Human well-being, and Production pillars depending on the landscape context and conditions, followed by a performance metric selection, prioritization process, and sustainability claiming. Our results portray that out of 21 indicators including core and landscape-dependent indicators in total 9 were determined as applicable, likewise, concerning metrics selection, 5 performance metrics were defined as required, 2 were recommended and 1 was optional. The company´s top prioritized indicators are ecosystem restoration (1.06 % of restored areas nationwide), household income (0.3 % nationwide = < $2.5/day), and health and nutrition (